2014
DOI: 10.2215/cjn.08640813
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trajectory of B-Type Natriuretic Peptide in Patients with CKD Stages 3 and 4, Dialysis, and Kidney Transplant

Abstract: Background and objectives B-type natriuretic peptide (BNP) concentration predicts outcome in patients undergoing dialysis. Because survival and cardiovascular risk change across the CKD continuum, serial changes in BNP were compared in patients at different CKD stages and after kidney transplantation.Design, setting, participants, & measurements Patients with CKD stages 3 and 4 (CKD 3-4), dialysis patients, and kidney transplant recipients (KTRs) from one center had two measurements of BNP taken a median of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…Although not statistically significant, our findings with BNP (and NT-proBNP) were dissimilar to these studies as the levels of these biomarkers increased over time in both groups, but to a greater degree if receiving carvedilol. This increase in BNP (and NT-proBNP) over time has been demonstrated in observational studies of dialysis patients [30, 31]. The major difference between these two intervention studies and our RCT was the much shorter duration of therapy in these studies (3 months in the carvedilol RCT and 4 months in the metoprolol study).…”
Section: Discussionsupporting
confidence: 57%
“…Although not statistically significant, our findings with BNP (and NT-proBNP) were dissimilar to these studies as the levels of these biomarkers increased over time in both groups, but to a greater degree if receiving carvedilol. This increase in BNP (and NT-proBNP) over time has been demonstrated in observational studies of dialysis patients [30, 31]. The major difference between these two intervention studies and our RCT was the much shorter duration of therapy in these studies (3 months in the carvedilol RCT and 4 months in the metoprolol study).…”
Section: Discussionsupporting
confidence: 57%
“…Roberts et al followed BNP levels in 48 patients with CKD, in 102 dialysis patients, and in 73 kidney transplant recipients for over five years and concluded that while temporal changes in BNP were predictive of survival in CKD, they did not predict survival in dialysis patients and kidney transplant recipients. 34 Similarly, Bodlaj et al measured NT-proBNP in 76 kidney transplant recipients before, shortly after and 2–3 weeks after transplant and found that NT-proBNP levels measured 2–3 weeks after transplantation were significantly correlated with eGFR at 1 year after transplantation. 35 However, these two patient populations differ from our patients who are more remote from the actual kidney transplantation with a median graft vintage of 4.0 years.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that elevation in hs‐TnT and association with cardiovascular outcomes in CKD is not merely because of decreased clearance, and may reflect other mechanisms such as underlying myocardial strain, endothelial dysfunction, or subendocardial ischemia in albuminuric CKD . NT‐pro‐BNP has been associated with death and cardiovascular events in CKD samples . Elevated BNP, which has a shorter half‐life than NT‐pro‐BNP, was associated with cardiovascular events in 1 Japanese cohort with known CVD .…”
Section: Discussionmentioning
confidence: 98%
“…These were limited by small sample sizes and event rates, inadequate control for confounding, and ethnic homogeneity . Moreover, few data are available evaluating the prognostic value of TnT measured with new high‐sensitivity assays (hs‐TnT) in CKD . Importantly, most prior studies do not include stages 1 to 2 CKD as defined by albuminuria with preserved glomerular filtration rate (GFR), when early interventions might make the largest impact on cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%